Boundary Struggles Contestations of Free Speech in the Norwegian Publis Sphere (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
Freedom of speech is a fundamental human right and a core value in liberal democracies. It is also, however, one of our time's most contested issues, constantly claimed to be either too wide-ranging, at the peril of vulnerable minority groups, or too limited, restricting dissent and democratic deliberation. Employing a sociological lens on the dynamics of the public sphere, this book investigates how the boundaries of free speech are contested and negotiated through social processes which silence certain groups and opinions while amplifying others. The book focuses on key topics in current free speech debates - immigration, religion and culture. Drawing on population-representative survey data, media analysis and in-depth interviews, the authors paint a broad picture of how boundaries of free speech are defined and maintained, experienced and challenged, in the rapidly changing Norwegian public sphere.